MEMPERKUAT NASIONALISME INDONESIA DI ERA GLOBALISASI - Listyarini, Dwi Ari (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2014)
Nationalism is a notion which argues that the loyalty of individuals should be left to the nation-state. Indonesian nationalism is the historical phenomenon that can not be removed from the influence of colonial powers of Western nations in the context of this colonial situation, the Indonesian nationalism is a response to the terms of political, socio-economic, cultural and specifically caused by the colonial situation. By kareka, then Indonesian nationalism in itself also contains three important aspects, namely political, economic social and cultural rights. From this statement it is understandable that if someone claimed a nationalist, then he must be willing to fight for the nation and state. This is condensed when the nation can traced Indonesia struggled to achieve independence, and maintaining independence. When in era of globalization, it seems that the values of Indonesian nationalism undermined by it. Globalization affects the various life of the nation of Indonesia, both in the field of ideology, political system or government, economics, social and cultural rights. Therefore, the essence of nationalism, Indonesia must continue to be maintained, namely the values of Pancasila, the 1945 Constitution, the love homeland, a sense of unity and unity and national insight. Also in an effort to strengthen nationalism in this era of globalization need to be pursued is a clean and authoritative government, instill and implement the teachings of religion with the best, instill and practice the values of Pancasila as well as possible, fostering the spirit of loving domestic production, and enforce rule of law to create justice for all Indonesian people.SimakBaca secara fonetik Key words: nationalism, globalization, the values of Pancasila